Enterovirus 71: pathogenesis, control and models of disease. (October 2012) - Xin, Khong Wei; Huimin, Yeo; Alonso, Sylvie
Enterovirus 71 (EV71) is one of the major agents responsible for hand, foot and mouth disease. The increasing incidence of hand, foot and mouth disease outbreaks, epidemics due to EV71 infection in South East Asia and the propensity of EV71 strains to cause severe neurological complications in young children underscore the need to further our knowledge and understanding of the mechanisms involved in EV71 pathogenesis; such knowledge could then be translated to the identification of biomarkers of disease severity, and the development of effective therapeutics and vaccines. This article reviews the current knowledge of EV71 pathogenesis, control measures and models of infection.